Fasudil ameliorates cognitive deficits, oxidative stress and neuronal apoptosis via inhibiting ROCK/MAPK and activating Nrf2 signalling pathways in APP/PS1 mice - Wei, Wenyue; Wang, Yuyin; Zhang, Jing; Gu, Qingfang; Liu, Xiaoqin; Song, Lijuan; Chai, Zhi; Guo, Minfang; Yu, Jiezhong; Ma, Cungen (Folia Neuropathologica, 2021)
Alzheimer’s disease (AD) is a severe neurodegenerative disorder of the central nervous system (CNS) characterized by neuron loss and dementia. Previous abundant evidence demonstrates that the first critical step in the course of AD is the state of oxidative stress and the neuronal loss is closely related to the interaction of several signalling pathways. The neuroprotective efficacy of Rho-associated protein kinase (ROCK) inhibitor in the treatment of AD has been reported, but its exact mechanism has not been well elucidated. The purpose of this study is to investigate the therapeutic effects of Fasudil on amyloid precursor protein/presenilin-1 (APP/PS1) mice and to discover the potential underlying mechanism. Sixteen 8-month-old APP/PS1 mice were divided into model and Fasudil treatment groups and 8 wild-type mice were used as a normal control group. After the behavioural test, all mice were sacrificed for immunofluorescence and other biochemical tests. The results showed that the administration of Fasudil improved learning and memory ability, elevated the concentration of antioxidative substances and decreased lipid peroxides, as well as inhibited neuronal apoptosis by increasing the expression of B-cell lymphoma-2 (Bcl-2) (p < 0.05), reducing Bcl-2 Associated X (Bax) (p < 0.05) and cleaved caspase-3 (p < 0.05) of APP/PS1 mice. Moreover, Fasudil treatment also ameliorated the phosphorylation of p38 (p < 0.01), c-Jun N-terminal kinase (JNK) (p < 0.001) and extracellular regulated protein kinases (ERK) (p < 0.001), and accelerated the nuclear factor-erythroid 2 p45-related factor 2 (Nrf2) (p < 0.01) expression and its antioxidative downstream molecules (p < 0.05, p < 0.05, and p < 0.05, respectively). Data from the present study demonstrate that Fasudil significantly restored cognitive function, restrained oxidative stress and reduced neuronal apoptosis in the hippocampus, probably by inhibiting ROCK/MAPK and activating Nrf2 signalling pathways in APP/PS1 mice.